Alkynes as Synthetic Equivalents of Ketones and Aldehydes: A Hidden Entry into Carbonyl Chemistry - Alabugin, Igor V.; Gonzalez-Rodriguez, Edgar; Kawade, Rahul Kisan; Stepanov, Aleksandr A.; Vasilevsky, Sergei F. (Molecules (Basel, Switzerland), 2019)
The high energy packed in alkyne functional group makes alkyne reactions highly thermodynamically favorable and generally irreversible. Furthermore, the presence of two orthogonal π-bonds that can be manipulated separately enables flexible synthetic cascades stemming from alkynes. Behind these “obvious” traits, there are other more subtle, often concealed aspects of this functional group’s appeal. This review is focused on yet another interesting but underappreciated alkyne feature: the fact that the CC alkyne unit has the same oxidation state as the -CH2C(O)- unit of a typical carbonyl compound. Thus, “classic carbonyl chemistry” can be accessed through alkynes, and new transformations can be engineered by unmasking the hidden carbonyl nature of alkynes. The goal of this review is to illustrate the advantages of using alkynes as an entry point to carbonyl reactions while highlighting reports from the literature where, sometimes without full appreciation, the concept of using alkynes as a hidden entry into carbonyl chemistry has been applied.